2010
DOI: 10.1111/j.1365-2265.2009.03664.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic chemerin is related to inflammation rather than obesity in type 2 diabetes

Abstract: SummaryBackground The adipokine chemerin modulates the function of innate immune cells and may link obesity and inflammation, and therefore, a possible relation of chemerin to inflammatory proteins in obesity and type 2 diabetes (T2D) was analysed. As visceral fat contributes to systemic inflammation, chemerin was measured in portal venous (PVS), hepatic venous (HVS) and systemic venous (SVS) blood of patients with liver cirrhosis. Patients and methods Systemic chemerin was determined by ELISA in the serum of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
194
4
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(228 citation statements)
references
References 31 publications
(76 reference statements)
22
194
4
8
Order By: Relevance
“…Studies in humans have demonstrated a strong correlation between circulating chemerin levels and markers of inflammation and the metabolic syndrome (Lehrke et al 2009, Spiroglou et al 2010, Weigert et al 2010, Dong et al 2011, Gao et al 2011, Ernst et al 2012). Yet, the circulating levels of TNFa and expression of proinflammatory cytokines in adipose tissue were not increased in ChemR23-deficient mice, even after they had been fed a HFD for 20 weeks.…”
Section: Figurementioning
confidence: 99%
“…Studies in humans have demonstrated a strong correlation between circulating chemerin levels and markers of inflammation and the metabolic syndrome (Lehrke et al 2009, Spiroglou et al 2010, Weigert et al 2010, Dong et al 2011, Gao et al 2011, Ernst et al 2012). Yet, the circulating levels of TNFa and expression of proinflammatory cytokines in adipose tissue were not increased in ChemR23-deficient mice, even after they had been fed a HFD for 20 weeks.…”
Section: Figurementioning
confidence: 99%
“…Chemerin is one of the ligands of CMKLR1 and circulating levels are increased in obesity (Meder et al, 2003;Weigert et al, 2010). Serum chemerin positively correlates with BMI, Homeostasis Model Assessment of Insulin Resistance, triglycerides, systolic blood pressure, leptin, resistin, C-reactive protein, TNF and IL-6 and negatively with HDL cholesterol suggesting a function of chemerin in metabolic disturbances associated with obesity (Bozaoglu et al, 2007;Parlee et al, 2010;Stejskal et al, 2008;Weigert et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The association between chemerin and diastolic dysfunction may be explained by the chronic inflammatory environment of psoriasis. Weigert et al [29] suggested that elevated serum chemerin was strongly related to CRP. Previous reports have shown that CRP decreases the production of nitric oxide and upregulates the expression of angiotensin type-1 receptor, which is associated with endothelial dysfunction [30,31].…”
Section: Discussionmentioning
confidence: 99%